2010
DOI: 10.1007/s10843-010-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Marketing externalities in industrial clusters: A literature review and evidence from the Christchurch, New Zealand electronics cluster

Abstract: Industrial cluster, Externality, SME, Exports, Networks, Internationalisation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…This is in agreement with Porter (1990) point of view that governments do have stakes in the influence of location in competition, to extend support to the people of that geographical area. The results are also consistent with the study by (Dögl et al, 2012;Deniz et al, 2013;Brown et al, 2010) that focused on designing of policies by the government concerning fields which are central to the well-being of public, like, health, environment, safety, institutional framework related to finance, industry, trade & business and development programs. The study further found out that regulations make the financial system more stable and reduce the risk of future financial crises.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with Porter (1990) point of view that governments do have stakes in the influence of location in competition, to extend support to the people of that geographical area. The results are also consistent with the study by (Dögl et al, 2012;Deniz et al, 2013;Brown et al, 2010) that focused on designing of policies by the government concerning fields which are central to the well-being of public, like, health, environment, safety, institutional framework related to finance, industry, trade & business and development programs. The study further found out that regulations make the financial system more stable and reduce the risk of future financial crises.…”
Section: Discussionsupporting
confidence: 91%
“…The governments, according to (Brown et al, 2010;Deniz et al, 2013;Dögl et al, 2012) design policies concerning fields which are central for the well-beinga of public, like, health, environment, safety, institutional framework related to finance, industry, trade & business and development programs. The government operates in geographical units through a range of different agencies which bring about their own influences on the business environment in the given locations.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Most related research has focused on developed countries of the Northern Hemisphere. Exceptions include Blandy's () reference to the wine‐making cluster in South Australia, Chetty and Campbell‐Hunt's () study of internationalization among 16 New Zealand firms, Hall's () study of New Zealand wine cluster and network development, Chetty and Agndal's () study of Auckland's boat‐building industrial district, the Dana and Winstone () study of a New Zealand wine cluster, and Brown, McNaughton, and Bell () about the electronics cluster in Christchurch; also relevant are Dana et al () and Felzensztein et al (). While there is agreement in the literature that clusters provide benefits to firms, especially value chain inputs and more general aspects of the production process (Mackinnon, Chapman, and Cumbers ), the relative contribution of regional clusters to new ventures and business growth is controversial (Fritsch and Mueller ) and may vary over time and from country to country (Acs, Desai, and Hessels ), presenting a lacuna and providing conflicting evidence on the benefits and positive externalities associated to regional clusters (Felzensztein and Gimmon ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the definition of the trade development organization, the export consortium is a voluntary combination of several companies that aim to demonstrate the art of exporting to its members, as well as increase the export capacity, expand the sale of goods and services abroad, and facilitate the export of these products through a participatory activity [6][7][8][9][10][11][12]. An export consortium is a collaboration between companies that allows individual companies to take advantage of opportunities in international markets due to globalization in a competitive environment.…”
Section: Export Consortiamentioning
confidence: 99%
“…Industrial clusters are new terms and concepts in the field of regional and industrial economics. In recent decades, industrial clusters have played a pivotal role in regional development in many developed and developing countries [7]. The industrial cluster was first introduced by Alfred Marshall in 1890.…”
Section: Industrial Clustersmentioning
confidence: 99%